2022
DOI: 10.5114/ada.2021.103327
|View full text |Cite
|
Sign up to set email alerts
|

The 2020 update on anaphylaxis in paediatric population

Abstract: The objective of the review is to present recent updates on anaphylaxis in paediatric population worldwide. The article summarizes the results of epidemiological studies, diagnostic methods and treatments. We present a new WAO definition of anaphylaxis (2019), which broader criteria excluding dermal symptoms should facilitate faster lifesaving adrenaline use. Adrenaline remains the best treatment to manage severe symptoms and to prevent biphasic reactions. There is ongoing effort to increase adrenaline use, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 72 publications
0
4
0
2
Order By: Relevance
“…According to a recent study, bronchial asthma is an independent risk factor for severe anaphylaxis [ 25 ]. Another study reported that having a history of asthma is strongly associated with severe anaphylaxis in children, especially in food-related anaphylaxis [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent study, bronchial asthma is an independent risk factor for severe anaphylaxis [ 25 ]. Another study reported that having a history of asthma is strongly associated with severe anaphylaxis in children, especially in food-related anaphylaxis [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anafilaksi, hızlı başlangıçlı ve ciddi sonuçları olan alerjik bir reaksiyondur. Bilinen ya da olası bir tetikleyiciden birkaç dakika ya da saat sonra gelişen dermal, respiratuvar, kardiyovasküler ya da gastrointestinal sistemin etkilendiği semptomlar görülür (1,2). Dünya Sağlık Örgütünün ICD-11'deki tanımına göre anafilaksi; yaşamı tehdit edebilen hava yolu, solunum veya dolaşım problemleriyle ani gelişen, genellikle cilt ve mukozal değişikliklerle ilişkili olan ciddi sistemik bir aşırı duyarlılık reaksiyonudur (3).…”
Section: Introductionunclassified
“…Hastaneye başvuruların %0,26'sı anafilaksi kaynaklıdır (6). Anafilaksi kaynaklı ölüm oranı %0,5-1 arasındadır (1). Bölge ve topluma göre değişmekle birlikte; anafilaksinin en sık sebepleri besinler, ilaçlar ve böcek sokmalarıdır (7).…”
Section: Introductionunclassified
“…Anaphylaxis is an allergic reaction characterized by symptoms affecting the dermal, respiratory, cardiovascular and gastrointestinal systems that develop within minutes or hours after a known or probable trigger 1 . In patients with anaphylaxis, skin and mucosal symptoms are most common (>90% of cases), followed by symptoms affecting the respiratory and cardiovascular systems (>50%) 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In children, the incidence for all-cause anaphylaxis is 1-761/100,000 person-years, while the incidence for food-induced anaphylaxis is 1-77/100,000 person-years 10 . Mortality rates due to anaphylaxis are between 0.5-1 1 The therapeutic dose of adrenaline is 0.01 mg/kg (1/1000). In treatment, adrenaline is administered intramuscularly into the vastus lateralis (thigh) muscle.…”
Section: Introductionmentioning
confidence: 99%